Re-examining the Nexus Between Maternal Smoking Behavior and Under-Five Children's ARI in India: A Comprehensive Study - Margubur Rahaman; Avijit Roy; Md Abdul Latif; Md Juel Rana; Pradip Chouhan; Kailash Chandra Das (SAGE Publishing, 2023)
Background: The burden of acute respiratory infections (ARIs) among children under-five is a serious concern in lower and middle-income countries (LMICs), including India, where it is positively associated with indoor smoking exposures. This study re-examines the impact of maternal smoking on ARIs among children under 5 in India, considering other indoor air pollutant factors and covariates. The aim is to establish existing findings and capture any differentials in results using comprehensive analytical approaches. Methods: Data from the National Family Health Survey (NFHS-5), 2019 - 21, was used. Descriptive statistics, bivariate analysis, multivariable logistic regression models, and interaction analysis were applied to accomplish the study objective. Results: The adjusted likelihood of ARI was 1.24 (95% CI: 1.04-1.48) times higher in under-five children with smoking mothers than those with non-smoking mothers. The result was also observed to be almost similar across all seasons. Moreover, the combined effect of maternal smoking with other household members smoking and using unclean cooking fuel without a separate ventilated kitchen escalated the risk (AOR: 2.01; 95% CI: 1.98-2.67). Breastfeeding was found to be a preventive measure for reducing the risk of indoor smoking exposure. The children who were never breastfed and were born large or small were more susceptible to maternal smoking. Conclusion: The study highlights the association between maternal smoking and ARIs in Indian under-five children. Interventions include reducing maternal smoking, promoting breastfeeding, and improving respiratory health in fuel-exposed households.